ANALISIS PENERIMAAN RETRIBUSI PARIWISATA JAWA TENGAH TAHUN 2015-2019 - Nina Setiarini; Rian Destiningsih (Jurnal Ekonomi-Qu, 2021)
Central Java Province is demanded to be able to explore the potential of the tourism industry sector, this is because the tourism industry sector is one that is relied on for the determination of the Central Java regional government. The tourism industry can be developed to obtain regional income through new innovations to raise regional expenditure funds through fees collected from each tourist location. From the analyst with the panel data method that has been done, it can be concluded that (1) number of tourism objects has a positive and significant effect on tourism levies, (2) number of tourists has no effect on tourism levies, (3) number of hotels has a negative and significant effect on tourism levies, and (4) variable number of tourism objects, number of tourists, and number of hotels influence the tourism levies in Central Java in 2015-2019 simultaneously.